Implementing and evaluating a citizen‐science program to support wildlife management: MI‐MAST - Alexander K. Killion; Gary J. Roloff; Sarah Mayhew; Henry Campa III; Scott Winterstein (Wildlife Society Bulletin)
ABSTRACT Citizen science is increasingly being used by natural resource professionals to monitor the environment at large spatial or temporal extents. Developing, initiating, and sustaining an effective citizen‐science program requires careful planning, marketing, and engagement. We describe the development, implementation, and evaluation of a citizen‐science program for quantifying mast production (called MI‐MAST: Wildlife Food Tracker), and offer recommendations on marketing, recruitment of volunteers, and ways to sustain programs. In 2014, MI‐MAST was introduced to approximately 150 potential participants to test technology and capabilities of volunteers. In 2015, we worked with project partners to market MI‐MAST to approximately 500 additional potential participants throughout Michigan, USA. From 2014 to 2017, 510 people registered for a MI‐MAST account, but only 57 people submitted data. On average, each person that submitted data entered 4 instances of mast production. We randomly field‐validated 60 mast observations submitted by 15 different participants throughout the study region and found that 100% of the plant species were correctly identified and 97% of the records describing mast amounts were accurate. The majority (61%) of registered users listed hunting as a primary outdoor interest. Interactions with participants revealed that using MI‐MAST to evaluate mast production on their own property was a primary attraction for enrollment and participation. We recommend that effective citizen‐science programs are marketed to provide personal benefits and tangible outputs to individual users. We found the biggest challenges facing a natural resource agency implementing a citizen‐science program to be recruitment and retention of participants across spatial and temporal extents that are ecologically meaningful. © 2018 The Wildlife Society.